Perbedaan Dukungan Keluarga Terhadap Ibu Yang Memberikan ASI Eksklusif Dan Non ASI Eksklusif Di Wilayah Kerja Puskesmas Sukorame Kecamatan Mojoroto Kota Kediri - Eny Sendra; Mika Mediawati; Amalia Afifi (Akademi Keperawatan Dharma Husada Kediri, 2016)
Exclusive breastfeeding has some benefits from some sides for the babies and their mothers. The intensity of exclusive breastfeeding at Puskesmas Sukorames’ work area in Kediri is still low and need some efforts to increase it. The objective of this research is to know the differences of family support towards mother who breastfeed exclusively and non-exclusively in Puskesmas Sukorames’ Work Area Mojoroto District Kediri City. This research used Retrospective approach and Case Control project which exclusive breastfeeding as the case and non-exclusive breastfeeding as the control group. Population used in this research were 335 exclusive breastfeeding respondents and 255 non-exclusive breastfeeding respondents by using Multi Stage Random Sampling was gotten 22 samples for exclusive breastfeeding and 11 samples for non-exclusive breastfeeding. Variable research was measured by a quisionaire consist of ten family supports. The result of Exact Fisher analysis was gotten p counted =0,09andα=0,05 (p counted > α) means H0 was accepted dan Ha was refused.The conclusion of this research was most of the respondent had high support to mother who breastfeed exclusively and the other most samples had low support to mother who breastfeed non-exclusively. So, there are no differences of family supports towards mother who breastfeed exclusively and non-exclusively in Puskesmas Sukorames’ Work Area Mojoroto District Kediri City. Keywords:Exclusive Breastfeed, Family, Family Support, Mother.